Pengaruh Service Quality, Customer Trust, dan Customer Satisfaction terhadap Purchase Intention Dalam Personal Selling Produk Asuransi Jiwa - Kurnia Utami Putri; Tri Inda Fadhila Rahma; Rahmi Syahriza (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research was made in purpose of examine and analyze the effect of service quality (SQ), Customer’s trust (CT) and satisfaction (CS) on purchasing decisions in the personal selling activities of PT. Prudential Sharia Life Assurance. The data was collected using a massive survey that had been created based on predetermined research indicators. The population in this research are active customers of PT. Prudential Sharia Life Assurance and as counted as 85 data of the respondents are used as the samples. The analytical method that had been used in this research is Structural Equation Modeling (PLS-SEM). The analytical results show that SQ, CT, and CS, along with personal selling have a significant effect on purchase intention. CS has a significant effect on personal selling, while SQ and CT have no significant effect on personal selling. Personal selling cannot mediate SQ and CT on PI. Personal selling can mediate CS on PI. Keywords: Service Quality (SQ); Customer Trust (CT); Customer Satisfaction (CS); Purchase Intention (PI); Life Assurance.